2022
DOI: 10.3390/molecules27103189
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Purification of Fucoxanthin from Phaeodactylum tricornutum

Abstract: Fucoxanthin is a natural marine xanthophyll and exhibits a broad range of biological activities. In the present study, a simple and efficient two-step method was used to purify fucoxanthin from the diatom, Phaeodactylum tricornutum. The crude pigment extract of fucoxanthin was separated by silica gel column chromatography (SGCC). Then, the fucoxanthin-rich fraction was purified using a hydrophile–lipophile balance (HLB) solid-phase extraction column. The identification and quantification of fucoxanthin were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These pigments possess several functional health properties such as antioxidant, anti-inflammatory, and skin photoprotective [ 7 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In vitro and in vivo studies highlighted both direct and indirect antioxidant and anti-inflammatory activity, through the modulation of specific genes and proteins [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These pigments possess several functional health properties such as antioxidant, anti-inflammatory, and skin photoprotective [ 7 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In vitro and in vivo studies highlighted both direct and indirect antioxidant and anti-inflammatory activity, through the modulation of specific genes and proteins [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Holdt and Kraan [ 103 ], the trans isomer has better stability, comprising 90% of naturally found fucoxanthin and has more potent antioxidants than the cis isomer. The structure of the fucoxanthin allenic bond is unique and imparts functional health impacts such as antioxidant, anti-obesity, anti-inflammatory, and many more [ 47 , 100 , 104 , 105 , 106 , 107 , 108 ]. The ability of fucoxanthin to modulate and alter the biological system of individual gene and protein expression is reported to be the key mechanism for its physiological activities [ 104 ].…”
Section: Potential Biological Activities Of Fucoxanthinmentioning
confidence: 99%
“…Furthermore, it has been shown to have dose-dependent antioxidant effects, with a 3.3-fold rise in the ratio of reduced to oxidised glutathione [ 106 ]. Recently, Zhao, et al [ 107 ] has reported that fucoxanthin purified by silica gel column chromatography (SGCC) has exhibited strong antioxidant properties, with effective concentrations of 0.14 mgmL −1 and 0.05 mgmL −1 for IC 50 of DPPH and ABTS free radicals, respectively.…”
Section: Potential Biological Activities Of Fucoxanthinmentioning
confidence: 99%
“… 13 Furthermore, fucoxanthin has been suggested to be safe by the European Food Safety Authority and the US Food and Drug Administration. 14 Fucoxanthin possesses unique structural features, including allene bond, epoxide and acetyl groups. 15 Due to its structural diversity, fucoxanthin has health benefits such as anti-inflammation, antioxidant, anti-obesity and anti-diabetic effects.…”
Section: Introductionmentioning
confidence: 99%